2015
DOI: 10.2139/ssrn.2609394
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Varying Degree of Inflation Expectations Anchoring

Abstract: Well-anchored inflation expectations have become a key indicator for the credibility of a central bank's inflation target. Since the outbreak of the recent financial crisis, the existence and the degree of de-anchoring of U.S. inflation expectations have been under debate. This paper introduces an encompassing time-varying parameter model to analyze the changing degree of U.S. inflation expectations anchoring. We confirm that inflation expectations have been partially de-anchored during the financial crisis. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Thus, we have four models, the results of which appear in Table 3. The results show a greater degree of anchoring in the medium term than in the short term, in line with the results of Carrasco and Ferreiro (2013), Strohsal, Melnick and Nautz (2015) or IMF (2016). The coefficient of past inflation becomes smaller and not significant in the second, third, and fourth years.…”
Section: Figure 11 Inflation Expectations From Focus Economicssupporting
confidence: 88%
See 4 more Smart Citations
“…Thus, we have four models, the results of which appear in Table 3. The results show a greater degree of anchoring in the medium term than in the short term, in line with the results of Carrasco and Ferreiro (2013), Strohsal, Melnick and Nautz (2015) or IMF (2016). The coefficient of past inflation becomes smaller and not significant in the second, third, and fourth years.…”
Section: Figure 11 Inflation Expectations From Focus Economicssupporting
confidence: 88%
“…Also, we use information from Focus Economics, which has data on inflation expectations up to five years ahead. Following the work of Łyziak and Paloviita (2016) and Strohsal, Melnick and Nautz (2015), we found that past inflation and short-term expectations do not have a significant impact. Meanwhile, the implicit target would be the main reference for the formulation of medium-term inflation expectations.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations